Pemanfaatan Pupuk Majemuk sebagai Sumber Hara Budidaya Tomat secara Hidroponik - Amalia Kusumawardhani; Winarso Drajad Widodo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
The objective of this research was to know the effect of compound fertilizer as nutrient source for hydroponics tomatoes. This experiment was conducted from Mei to September 2002, at Cikabayan Experiment Station of The Faculty of Agriculture, Bogor Agriculture Institut (IPB). The compound fertilizers used were Grow More, Gandapan, Hyponex, and Joro AB mix as control. Experimental design used was Randomized Block Design with three replications. The results of this experiment indicated that Joro and Gandapan have the greatest effect for vegetatif phase. There was no significant difference between control (Joro) and the treatments (Grow More, Gandapan, and Hyponex) in number of flower, fruit set, fruit weight, and bad fruit weight, fruit quality, percent total solid. This indicated that the fertilizers could be used as nutrient source for tomato cultured in hydroponics.  Key words : Hydroponic, Multi fertilizer, Vegetatif, Generative phase.